Transient Frequency Estimation Methods for the Fast Frequency Response in Converter Control - Pfendler, Anna; Steppan, Rafael; Hanson, Jutta (Electronics (Basel), 2023)
In an interconnected power system, frequency control and stability are of vital importance and indicators of system-wide active power balance. The shutdown of conventional power plants leads to faster frequency changes and a steeper frequency gradient due to reduced system inertia. For this reason, the importance of electrical frequency estimation methods is increasing, among others, as an input for the control of converter-based generation plants. The aim of this work is to implement, compare, and analyze the robustness of the Phase-Locked-Loop and Zero-Crossing, Gauss–Newton, and recursive Gauss–Newton methods in time-domain simulations in Matlab/Simulink. The parameters of these methods are tuned for different scenarios in a medium-voltage testbench. The sensitive parameters of the frequency estimation methods show a linear correlation to the magnitude of the active power imbalance so a simple implementation can be designed for simulations. With the linearized parameter calculation for the frequency estimation methods, the local frequency as an input for converter control is used for the fast frequency response of a full power converter, which counteracts frequency deviations in the power system. Finally, two different implementations of the fast frequency response are compared. The Zero-Crossing Method shows the best robustness and the Phase-Locked Loop achieves the absolute best result.